The Influence of Hedonic Shopping, Motivation Promotion on Impulse Buying Which Impact on Shopping Lifestyle - Yuda Supriatna; Amarul Amarul; Sabrina Handayani Pemungkasih (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This research aims to analyze the influence of Hedonic Shopping Motivation and Promotion on Impulse Buying and Shopping Lifestyle. The research results show that Hedonic Shopping Motivation does not have a significant influence on Impulse Buying and Shopping Lifestyle with significance values of 0.835 and 0.793 (> 0.05) respectively. On the other hand, Promotion has a significant influence on Impulse Buying and Shopping Lifestyle with significance values of 0.004 and 0.000 (< 0.05) respectively. Additionally, Impulse Buying also has a significant influence on Shopping Lifestyle with a significance value of 0.000 (< 0.05). Path analysis reveals that the indirect influence of Hedonic Shopping Motivation is through Impulse Buying on Shopping Lifestyle is not significant, while the indirect influence of Promotion through Impulse Buying towards Shopping Lifestyle is significant. These findings emphasize the importance of promotional strategies in influencing consumer impulse shopping behavior and shopping lifestyles, and demonstrate the need for new approaches in understanding hedonic shopping motivations.